Histological and radiological evaluation of thermal denaturation depth using soft coagulation during partial nephrectomy in living pigs. (10th August 2021) - Fujisaki, Akira; Takayama, Tatsuya; Teratani, Takumi; Kubo, Taro; Kamei, Jun; Sugihara, Toru; Ando, Satoshi; Morita, Tatsuo; Fujimura, Tetsuya
Abstract : Objectives: To evaluate thermal denaturation depth using soft coagulation in kidneys in vivo . Methods: In experiment 1, nine kidneys from five pigs were cauterized using five soft‐coagulation settings at 80 W with effect 7 by VIO300D and one monopolar‐coagulation setting. The surface of the kidney was cauterized over a period of 2, 5 and 10 s. The temperature change was measured at depths of 5 and 10 mm. In experiment 2, three kidneys from two pigs were excised in a semicircular shape with a diameter of 5, 10 and 20 mm without clamping the renal artery. Cauterization was carried out until hemostasis was confirmed by soft coagulation at 80 W with effect 7. After completion of the experiments, pathology examinations of the kidneys were carried out. Results: Experiment 1 showed that with proper saline dripping, denaturation spread with increased cauterization time, reaching a depth of 4 mm at 10 s with or without clamps. The depth remained at 2–3 mm at 10 s in the absence or excess of saline. The temperature increased by 15.6°C at a depth of 5 mm and 8.8°C at 10 mm. In experiment 2, the depth was 4.6 mm from the incision surface regardless of the cauterization time or excision size. Conclusions: These findings suggest that soft coagulation can be useful for preserving renal function and reducing complications in partial nephrectomy.